Effects of the Combined Treatment of Extracorporeal Shock Wave Therapy (ESWT) and Stabilization Exercises on Pain and Functions of Patients with Myofascial Pain Syndrome - Park, Soo-Jin; Choi, Young-Chul; Jang, Sang-Hun; Cho, Young-Shin; Lee, Jung-Ho; Kim, Jin-Sang (Journal of Physical Therapy Science, 2012)
[Purpose] In order to develop a more effective treatment method for pain and function in myofascial pain syndrome, we examined the effects of ESWT, stability exercises, and combined treatment. [Subjects] The subjects were randomly divided into a stabilization exercise group (n=12), an ESWT (Extracorporeal Shock Wave Therapy) group (n=12), and a combined treatment group (n=12). [Methods] The stabilization exercise group performed shoulder joint stabilization exercises. The ESWT group received ESWT for the upper trapezius. The combined treatment group received a combined treatment of shoulder joint stabilization exercises and ESWT. Pain and function were measured using the visual analog scale (VAS), pressure pain threshold (PPT), neck disability index (NDI), and the Constant Murley Scale (CMS). [Results] The VAS Score showed statistically significant improvements in all of the groups. All of the CMS evaluation items except muscle strength in the stabilization exercise group, and all of the CMS items in the ESWT group and the combined treatment group, exhibited statistically significant improvements. The combined treatment group of ESWT and stabilization exercises showed statistically significant improvements in all VAS of CMS evaluation items, and the NDI test after the four-week intervention. [Conclusion] The combined treatment was more effective at reducing pain than ESWT, and stabilization exercise would be useful for physical therapists treating myofascial pain syndrome in a clinical setting.